Analisis Daya Dukung Lahan Untuk Mendukung Pengembangan Kawasan Berbasis Ekowisata - Syariah, Arfiani (EMARA Indonesian Journal of Architecture, 2016)
Indonesia with the very broad span its land, posses a large number of locations that feasible to be develop as a tourism area for supporting the economy of its cities. One of them that potentially to be develop is Bukit Surowiti in Gresik, East Java. Until recently Bukit Surowity only be used as pilgrimage tourism area, with high frequent visitors only happened at certains times of occasion. With the hilly topography condition, the area could offer an alternative type of tourism to be develop. An area itself can be said sustainable if it is supported by the ability to maintain and improve the environmental sustainability as of community economic through direct involvement for tourism development. This The aim of this studyÂ were to analyzed the Bukit Surowity physical condition and identifying areas that have the most appropriate land-carrying capacity for tourism facilities and supporting infrastructure for Bukit Surowiti development. The identification was conducted through a field surveys and land characteristics zoning based on the potential of topography, viewing zones and existing vegetation for the need of further analysis and mapping through carrying capacity ratio method. The analysis and mapping result generate a map of land development feasible location that can become reference for the local government in determining the direction of Bukit Surowiti tourism area development.